2011
DOI: 10.1007/s00228-011-1066-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of caspofungin in a critically ill patient with liver cirrhosis

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The AUC 0 -24 was low in both patients, and the dose was increased to 50 mg, after which the AUC 0 -24 was adequate and liver enzymes remained stable. These results are in accordance with two case reports where 50 mg and 70 mg were given to patients with moderate hepatic dysfunction and where the exposure was similar to the exposure in healthy volunteers (39,40). These findings illustrate that liver drug metabolism may be underestimated in the presence of liver test abnormalities or evidence of cirrhosis (41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The AUC 0 -24 was low in both patients, and the dose was increased to 50 mg, after which the AUC 0 -24 was adequate and liver enzymes remained stable. These results are in accordance with two case reports where 50 mg and 70 mg were given to patients with moderate hepatic dysfunction and where the exposure was similar to the exposure in healthy volunteers (39,40). These findings illustrate that liver drug metabolism may be underestimated in the presence of liver test abnormalities or evidence of cirrhosis (41).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the results of that study, the authors state that the caspofungin maintenance dose should not be reduced in noncirrhotic ICU patients based on the Child-Pugh score if the classification is driven by hypoalbuminemia, as the decreased maintenance dose results in a significantly lower caspofungin exposure (42). Combined with the case reports and recent study (39,40,42), our findings suggest that patients with moderate hepatic dysfunction should perhaps initially receive a higher empirical maintenance dose, with close follow-up with therapeutic drug monitoring (TDM) and monitoring of liver enzymes. Further research in this patient group is needed to provide evidence for the development of new dosing recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Renal function seems to be crucial in the prognosis of patients with severe AH [25]. Caspofungin is metabolized by the liver, but recent small studies have suggested that it is not toxic and is effective in patients with liver failure [26,27]. However, the ability of caspofungin to penetrate into the cerebrospinal fluid is poor, and cerebral aspergillosis was found in one quarter of our IA patients [28].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, case reports of patients with mild-to-moderate hepatic impairment treated with caspofungin 70 or 50 mg q.d. showed that dose reductions to 35 mg would possibly have lead to suboptimal exposure of caspofungin [91][92][93].…”
Section: Anidulafunginmentioning
confidence: 99%